Replacement of Lost CNS Function - Vinall, Phil (MD Conference Express, 2008)
This article discusses updates in stroke recovery therapies, including an overview of the current state of Functional Electrical Stimulation, which is the use of electrical stimulation (via a neuroprosthesis) to activate muscles in a specific programmed sequence to allow the functional use of a limb that has been affected by stroke or spinal cord injury. Also discussed are advances in the BrainGate Neural Interface System, and the development of an interactive robot-assisted neuro-rehabilitation system called RUPERT (Robotic Upper Extremity Repetitive Trainer).